THE INDEPENDENCE AND ACTIVENESS (KEMANTI) – BASED ACTIVE LEARNING STRATEGY TO IMPROVE COOPERATION AND LEARNING OUTCOMES - Bambang Sudarsono (VANOS Journal of Mechanical Engineering Education, 2018)
This research was aimed to find out the improvement of cooperation and student learning outcomes by implementing active learning strategies based on the independence and activeness (KEMANTI). The design of this research adopted Classroom Action Research. The learning strategy of KEMANTI was applied in SMK Muhammadiyah 1 Salam Magelang. The stages of research resulted in the improvement of student cooperation can be seen from each aspect of cooperation which includes aspect of giving idea or opinion up 30%; accepting the opinion of others up 50%, carrying out the tasks given by the group up 30%, the nature of helping others up 40%, and the last aspect is concern for the difficulties of fellow group members up 50%. Improvement of student learning outcomes is shown by the value of effect size 3.2. The difference in learning outcomes uses t Test which shows that t tab is 4.9 in cycle I and t tab is 16,9 in cycle II. Test Results t post-test cycles I and II t hit> t tab is 15.00> 2.0. The conclusion of the t test results is that there is a difference from pre-test and post-test in cycle I and cycle II after being given an active learning strategy of KEMANTI.